Penggunaan Alat Pelindung Diri (APD) Masker Dengan Gangguan Saluran Pernapasan Pada Pekerja Di PT Bokormas Kota Mojokerto - Abdul Muhith; Mujib Hannan; Nurul Mawaddah; Citra Astri Aqnata (Fakultas Ilmu Kesehatan, 2018)
Indonesia has an interest in Health and Safety. One of them is the increasing of occupational diseases due to the combination of various factors ie labor and work environment such as dust, steam, and gas that can disrupt productivity and health. The purpose of this study is to analyze the relationship between the use of personal protective equipment (PPE) mask with respiratory disorders in workers at PT. Bokormas Mojokerto City. This research use analytic survey method with cross sectional approach with sampling technique used is simple random sampling with research object amounting to 47 workers in part Process SKAND Subscription, Patri, Tobacco Process, Tobacco Process II. Data collection using questionnaire use PPE Mask and respiratory disruption and observation sheet. Data were analyzed by Spearman Rank correlation test. The study was conducted from February to April 2017.The result of the research shows that most of PT Bokormas workers have negative behavior in the use of personal protective equipment more that is (51,1%) and most of the workers have respiratory diseases complaints in category ≥ Average that is 25 people.Calculation of Spearman Rank statistical test with a significant level value α = 0.05 obtained results r = 0.013. Which means smaller than the significant level (0.031 <0.05) then H0 is rejected. There is a significant relationship between the use of mask self-protective equipment with respiratory disorders in workers of PT Bokormas Mojokerto City.It is expected that PT Bokormas workers have a positive attitude in using mask self-protective equipment, then it will be able to reduce or minimize the risk of disruption or disease associated with the respiratory tract.